Student’s general attitude in gender-inclusive language - Ma. Theresa R. Remigio; Arlene D. Talosa (International Journal of Evaluation and Research in Education (IJERE), 2021)
Centered on studies on language and gender, this study generally aimed to assess the students’ general attitude towards Gender-Inclusive It likewise determined difference on attitude when grouped according to sex. The study utilized quantitative research design. Survey questionnaire using the IASNL was the instrument used which assesses beliefs, recognition of sexist language and willingness to use gender-inclusive language. Respondents utilized were randomly selected students of the College of Teacher Education. Results revealed that most of the students were female, displaying a positive attitude towards gender-inclusive language which indicates the students’ openness to gender-inclusive language use. It was found though that women and men did not seem to care strongly one way or another about gender-inclusive language. The result is reflective of the potential positive feedback to the Gender and Development (GAD) mainstreaming programs of the campus on the use of the said language.